2010
DOI: 10.1007/s00134-010-1824-6
|View full text |Cite
|
Sign up to set email alerts
|

Attributable mortality of ventilator-associated pneumonia: respective impact of main characteristics at ICU admission and VAP onset using conditional logistic regression and multi-state models

Abstract: A multistate model that appropriately handled VAP as a time-dependent event produced lower VAP-AM values than conditional logistic regression. VAP-AM varied widely with case-mix. Disease severity at VAP onset markedly influenced VAP-AM; this may contribute to the variability of previous estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(115 citation statements)
references
References 35 publications
9
98
1
5
Order By: Relevance
“…However, in an unselected ICU population, it has been suggested that late-onset pneumonia and not early-onset pneumonia can be associated with excessive mortality. 27,31,32 The SAPS II score, serum lactatemia, and vasopressor requirements on ICU admission were significantly higher in patients who developed E-HAP. They also required immediate postoperative mechanical ventilation exceeding 2 days more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an unselected ICU population, it has been suggested that late-onset pneumonia and not early-onset pneumonia can be associated with excessive mortality. 27,31,32 The SAPS II score, serum lactatemia, and vasopressor requirements on ICU admission were significantly higher in patients who developed E-HAP. They also required immediate postoperative mechanical ventilation exceeding 2 days more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analyses that attempted to match subjects with VAP to similar subjects without VAP, to adjust for important comorbidities, and/or to employ novel statistical strategies to overcome these sources of bias generated much lower estimates of the attributable mortality of VAP. [10][11][12] Furthermore, if VAP is only responsible for a small fraction of ICU mortality, this begs the question of whether focusing quality improvement efforts on VAP detection and prevention alone is the best way to improve outcomes for ventilated populations. 13 What about all of the other common and morbid conditions that can develop in ventilated patients, such as ARDS, pulmonary edema, severe sepsis, thromboembolic disease, and others?…”
Section: Limitations Of Vap As a Quality Metric For Ventilated Patientsmentioning
confidence: 99%
“…The originality of the present study lies in the description of OD/F over the entire ICU course using a score developed for that purpose [12]. Thus, it differs from recent studies on severity of sepsis or VAP that measured SOFA score [18], a new score called VAP-PIRO [19], or the LOD score [20] from the day of infection. In our study, we found that delta SOFA related to ICUAP explained only 10.3% of the SOFAmax which was by far lower than the contribution of SOFApreICUAP (the sum of SOFA-D1 and deltapreICUAP), which accounted for 87.5% of SOFAmax (Fig.…”
Section: Discussionmentioning
confidence: 99%